Cover Feature: Metallic Nanoparticle‐Enabled Sensing of a Drug‐of‐Abuse: An Attempt at Forensic Application (ChemBioChem 17/2020). (19th August 2020) - Hu, Ming; Han, Qinyu; Xing, Bengang
Abstract : Making partying safer . γ‐Hydroxybutyric acid (GHB) has gained attention as a drug that is frequently misused in social settings to induce euphoria and to facilitate sexual assault. A simple approach for selective sensing of GHB has been developed for drug screening and forensic investigation. Such a strategy, based on a specific enzymatic reaction, allows GHB to be analyzed in a complicated sample matrix, including biological specimens. The results can be readily acquired by either spectral assay or observation with the naked‐eye. More information can be found in the full paper by B.‐G. Xing et al. This cover was designed by using resources from www.Freepik.com.